1993
DOI: 10.1104/pp.102.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Endopolygalacturonase in Apples (Malus domestica) and Its Expression during Fruit Ripening

Abstract: The activity of polygalacturonase (PC) has been detected in ripe Mclntosh apples (Malus domestica Borkh. cv Mclntosh) both by enzyme activity measurement and immunoblotting using an antitomato-PC antibody preparation. PC activity increased during fruit ripening and remained steady, or decreased slightly, after 5 months of controlled atmospheric storage. l h e enzyme had a relative molecular weight of 45,000 as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and 56,000 to 61,000 when det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…This pattern of expression parallels that reported for PG enzyme activity by Wu et al (1993). The coding region of pGDPG-1 contains 460 amino acids and shows 52, 55, and 62% identity to endo-PG genes from tomato, avocado, and kiwifruit, respectively.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…This pattern of expression parallels that reported for PG enzyme activity by Wu et al (1993). The coding region of pGDPG-1 contains 460 amino acids and shows 52, 55, and 62% identity to endo-PG genes from tomato, avocado, and kiwifruit, respectively.…”
supporting
confidence: 52%
“…Recently, however, the activity of endo-PG has been detected in apple (Wu et al, 1993). These authors also reported cross-reactivity between an anti-tomato-PG antibody and a protein in apples of M, 45,000.…”
mentioning
confidence: 83%
“…Alternatively, PG activity may be present but at as-yet-undetectable levels. For example, apple pectins are disassembled at the late stages of ripening (Knee, 1973), and recently, under rigorous examination, endo-PG activity and PG mRNA accumulation have been detected but the levels are much lower than that observed in tomato (Wu et al, 1993).…”
Section: Pg Activity In the Fruit Of Other Plant Speciesmentioning
confidence: 99%
“…The enzyme originally considered responsible for pectin solubilisation and therefore softening in most fruits was polygalacturonase (PG), with activities of both exo-PG and endo-PG detected in ripening apples (Bartley 1978;Wu et al 1993;Atkinson et al 1998). Electron microscopy revealed that treatment of unripe apple discs with PG caused similar disruption in the middle lamella to that observed in ripe apple tissue (BenArie et al 1979).…”
Section: Cell Wallmentioning
confidence: 99%